GAYA KEPEMIMPINAN KEPALA SEKOLAH DALAM MENJALANKAN FUNGSI MANAJEMEN - Jiwa Marisya Amsor (Jurnal Tata Kelola Pendidikan, 2021)
This research is entitled Analysis of Principal Leadership Style in Carrying Out Management Functions in State Senior High School 1 Baleendah. The purpose of this study was to describe the tendency of the principal's leadership style in State High School 1 Baleendah, Bandung Regency. This research is a qualitative research with a descriptive approach. Sources of data in this study were the principal, vice principal of the curriculum field. deputy principal for student affairs, deputy principal in the field of infrastructure, deputy principal in the field of public relations, teachers, and administrative staff. The data technique used interviews, observation and documentation study. Data were analyzed by reducing data, presenting data and drawing data in narrative form. The results showed that: the leadership style used by the principal of State Senior High School 1 Baleendah tended to use democratic amd participative leadership. 1) The leadership of the principal, including the planning process, tends to use a democratic and visionary leadership style. 2) The organizing process tends to be carried out in a democratic and participative leadership style. 3) The implementation process tends to be carried out with a task-oriented leadership style and human relations that prioritizes cooperative relations and general and personal direction and guidance. 4) The process of supervision tends to be carried out with delegative leadership style by supervising directly and giving trust to subordinates to supervise so as not to continuously supervise by going around the classroom, overseeing the performance of teachers and employees.